The functional status of the prooksidant and antioxidant systems in the liver in the dynamics of formation of experimental pneumonia - Ferents, Nataliya M. (Journal of Education, Health and Sport, 2015)
Ferents N. M. The functional status of the prooksidant and antioxidant systems in the liver in the dynamics of formation of experimental pneumonia. Journal of Education, Health and Sport. 2015;5(10):180-184. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32599 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A180-184 https://pbn.nauka.gov.pl/works/661362 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. UDC: 61624 - 002 -036.11 - 092: 612,015 THE FUNCTIONAL STATUS OF THE PROOKSIDANT AND ANTIOXIDANT SYSTEMS IN THE LIVER IN THE DYNAMICS OF FORMATION OF EXPERIMENTAL PNEUMONIA N. M. Ferents Lviv National Medical University Daniel Galician, Lviv, Ukraine Abstract Pneumonia occupies a large share in the structure of the respiratory disease. Today in practice physician often found both hypo- and overdiagnosis pneumonia. Over the past thirty years, mortality from pneumonia increased from 1 to 9% and most often occurs in people older than 55 years of age. The study was conducted on 40 guinea pigs (male) weighing 180-220 g. The experimental model of pneumonia by intranasal infection reproduced animals culture Staphylococcus Aureus method. The results of the studies found that on 1st day staphylococcus infection animal control and MDA content not experienced significant changes to intact animals. Experimental pneumonia accompanied by noticeable imbalance between prooxidant and antioxidant systems towards growth inhibition of oxidative and antioxidant systems. Keywords: experimental pneumonia, liver, lipid peroxidation, antioxidant system.